Best Answer

5x-4y+9y+x-9+7 = 5x + x - 4y + 9y - 9 + 7 = 6x + 5y - 2 ■

Q: What is the answer to 5x - 4y plus 9y plus x -9 plus 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

4y + 10 = -18 4y = -28 y = -7

4y - 6y + 9y = -2Combine like terms on the left side:7y = -2Divide each side by 7:y = -2/7The solution set is: { -2/7 }

8x-7 plus 2x equals 6 plus 5x plus 2?

-6x+3 = -7-5x 7+3 = 6x-5x 10=x

-7+11x = 9-5x 11x+5x = 9+7 16x = 16 x = 1

Related questions

7(5x + 9y)

4y + 10 = -18 4y = -28 y = -7

7(5x + 4y)

YES : Equation (1) 5x - y = 3x + 9y = 19 : Multiply by 5 â†’Equation (2) 5x + 45y = 95Subtract Equation (1) from Equation (2) to eliminate 'x' terms. This gives : 45y -(-y) = 95 - 3 : 46y = 92 : y = 2Substituting for y in Equation(1) gives : 5x - 2 = 3 : 5x = 3 + 2 = 5 : x = 1Substituting for x and y in the equation 3x + 4y - 6c = -7 gives : 3 + 8 - 6c = -7 : 6c = 11 + 7 = 18 : c = 3

4y - 6y + 9y = -2Combine like terms on the left side:7y = -2Divide each side by 7:y = -2/7The solution set is: { -2/7 }

It is an algebraic expression that can be simplified to: 5x+9y+5

5y - 3 = 4 + 9y Subtract 5y from both sides: -3 = 4 + 4y Subtract 4 from both sides: -7 = 4y Divide both sides by 4: -7/4 = y

If: 5x-9y = 7 and 7y-3x = -5 Then: x = 1/2 or 0.5 and y = -1/2 or -0.5

1. 6x - 5y = 22 2. 5x - 9y = -1 1 times 5: 30x - 25y = 110 2 times 6: 30x - 54y = -6 Subtract : 29y = 116, so y = 4 and x therefore = 7

4y + 7 < 3y + 9 4y - 3y < 9 - 7 y < 2

5x(raised to the 2) +4x -9y

5x + 2y = 4 (Eq1) -5x + 2y = -10 (Eq2) Add the two equations 4y = -6 so y = -1.5 x = (4 - (2 x -1.5))/5 = (4 + 3)/5 = 7/5 = 1.4 Check: 5 x 1.4 + 2 x -1.5 = 7 - 3 = 4; -5 x 1.4 + 2 x - 1.5 = -7 - 3 = -10 QED